Oxidative Stress and Antioxidant Vitamins Status in Patients with Urolithiasis from North Eastern Part of India - Renthlei, Lawmzuali; Singh, Nongmaithem Mohondas; Lalruatfela, ST; Singh, Kshetrimayum Birla (Asian Journal of Biological and Life Sciences, 2016)
There is high prevalence of urolithiasis in the natives of the North Eastern part of India and required urgent attention. The present study was conducted with an aim to assess the state of oxidative stress and antioxidant vitamins status in patients with urolithiasis from North Eastern Region of India as there is no clinical data to date in the patients with urolithiasis from this region of India. In the present study 50 subjects diagnosed with urolithiasis were included after obtaining informed consent. Plasma levels of lipid peroxidation (LPO), vitamin-E (α- tocopherol) and vitamin-C (ascorbic acid), erythrocyte superoxide dismutase (SOD) and catalase (CAT) activities were measured. These findings were compared with 40 age matched control subjects irrespective of sex. A significant increased in LPO products as indicated by malonylaldehyde (MDA) level (p<0.001), and significant reduction in SOD and CAT activities (p<0.001) was observed in the patients subjects as compared to control. Whereas non significant decreased (p>0.05) in the plasma vitamin-E and vitamin-C were also recorded in patients than those of the control. The result of the present study suggests that oxidative stress is an evident and bearings in pathogenesis of urolithiasis with depletion in antioxidant status.
Keywords: Antioxidant Enzymes; Antioxidant Vitamins; Oxidative stress; Urolithiasis